Impact of Mach number on the flow pattern in suddenly expanded duct. (2022) - Khan, Sher Afghan; Chaudhary, Zakir Ilahi; Baig, Maughal Ahmed Ali; Ridwan,; Delvi, Hamza Afser; Faheem, Mohammed
Abstract: A study is undertaken to assess the dynamic control's effectiveness at two supersonic Mach numbers, 2.2 and 2.58 being considerably large Mach number being very significant in the design of High-speed aerospace vehicles. The relief available to the flow while the shear layer exits from the nozzle and enters the enlarged duct. The investigation area ratio is 4.84, and the NPR tested is from 3 to 11, covering the various level of expansion. The investigation was done for eight sizes of circular duct cases. Still, the results are discussed only when a significant change in the wall pressure is noticed during the experimentation. The dynamic control is located at a 6.5 mm radial distance from the primary jet's axis, with a 1 mm diameter generating at sonic Mach from the active flow control management. For lower duct length at NPRs, the wall pressure assumes large values. Later, with a rise in the duct section and NPR, a progressive decline in the pressure values is seen due to the decrease in adverse pressure levels and the intensity of the oblique shock waves. The duct flow mild oscillations are seen for duct section 3D, 5D, 6D, and 10D. The duct length portrays a crucial role while determining the stream development in the enlarged circular tube. When the duct's size is 6D and 10D, the low wall pressure is seen. For NPR = 5, the wall pressure takes moderate values due to the influence of the tube. At NPR = 7, 9, and 11, the pressure rise is limited within the reattachment zone, and ambient conditions are nearly attained within a short duct length. Despite nozzles, they are over-expanded flow control effects in a rise of pressure at Mach 2.58 for duct size 6D and 10D. For the duct size 10D, the attainment of ambient pressure is further advanced towards the upstream.